Epidemiological characteristics of tuberculosis patients under followed by Nevsehir community health center - Kolutek, Rahsan; Muslu, Leyla (Annals of Medical Research, 2021)
Aim: The aim of the study is to contribute to epidemiological data related to tuberculosis in Turkey by analyzing the epidemiological characteristics of patients registered in the Nevşehir Community Health Center Tuberculosis Unit.Material and Methods: In this study which is descriptively typed, the data of the registered patients between January 2011 and December 2017 in the Tuberculosis Control Unit of the Public Health Center of Nevsehir were retrospectively analyzed. The demographic characteristics and tuberculosis-related characteristics of the patients and the distribution of Tuberculosis patients by years were scanned through Electronic Tuberculosis Management System and related documents and the results were evaluated electronically. Results: 53,6% of the patients were diagnosed with pulmonary tuberculosis. Nurse, dental technician, soldier, prisoner, student, and masseur were among the occupations that had the risk of spreading tuberculosis. It was determined that 18.6% of them actively smoked. In this study, the number of asylum seekers having Tuberculosis disease was found as 6,4%. and pulmonary tuberculosis rate was found significantly higher in men. Additionally, the disease was found to be significantly more common in the rural districts.Conclusion: At the end of the study, it was determined that the patients with tuberculosis lived in low income and crowded families and in unfavorable locations. It was recommended that primary precautions should be taken according to the risk of the disease spreading at the rural district where the number of cases was the highest.
Keywords: Community health; epidemiology; tuberculosis